2011
DOI: 10.1128/jvi.01107-10
|View full text |Cite
|
Sign up to set email alerts
|

Structural Features of the Seneca Valley Virus Internal Ribosome Entry Site (IRES) Element: a Picornavirus with a Pestivirus-Like IRES

Abstract: The RNA genome of Seneca Valley virus (SVV), a recently identified picornavirus, contains an internal ribosome entry site (IRES) element which has structural and functional similarity to that from classical swine fever virus (CSFV) and hepatitis C virus, members of the Flaviviridae. The SVV IRES has an absolute requirement for the presence of a short region of virus-coding sequence to allow it to function either in cells or in rabbit reticulocyte lysate. The IRES activity does not require the translation initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
88
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 53 publications
0
88
0
Order By: Relevance
“…These elements are cis-acting RNA regulatory sequences endowed with the capacity to govern cap-independent translation initiation in mRNAs that are translated when cap-dependent translation is compromised. Subsequent studies demonstrated that IRES elements drive internal initiation of translation in the RNA of all members of the Picornaviridae family (Bakhshesh et al, 2008;Borman and Jackson, 1992;Brown et al, 1991;Hinton and Crabb, 2001;Hinton et al, 2000;Kaku et al, 2002;Kuhn et al, 1990;Nateri et al, 2000;Sweeney et al, 2012;Willcocks et al, 2011;Yu et al, 2011b). The genome of other RNA viruses also contains IRES elements, as illustrated by hepacivirus, pestivirus, dicistrovirus, retrovirus Tsukiyama-Kohara et al, 1992;Vallejos et al, 2010;Wilson et al, 2000), as well as some RNA viruses infecting plants and protozoa (reviewed in Martinez-Salas et al, 2012).…”
Section: Features Of the Picornavirus Untranslated Regionmentioning
confidence: 99%
“…These elements are cis-acting RNA regulatory sequences endowed with the capacity to govern cap-independent translation initiation in mRNAs that are translated when cap-dependent translation is compromised. Subsequent studies demonstrated that IRES elements drive internal initiation of translation in the RNA of all members of the Picornaviridae family (Bakhshesh et al, 2008;Borman and Jackson, 1992;Brown et al, 1991;Hinton and Crabb, 2001;Hinton et al, 2000;Kaku et al, 2002;Kuhn et al, 1990;Nateri et al, 2000;Sweeney et al, 2012;Willcocks et al, 2011;Yu et al, 2011b). The genome of other RNA viruses also contains IRES elements, as illustrated by hepacivirus, pestivirus, dicistrovirus, retrovirus Tsukiyama-Kohara et al, 1992;Vallejos et al, 2010;Wilson et al, 2000), as well as some RNA viruses infecting plants and protozoa (reviewed in Martinez-Salas et al, 2012).…”
Section: Features Of the Picornavirus Untranslated Regionmentioning
confidence: 99%
“…Therefore, eIFs and ribosomal subunits were purified from HeLa cells according to described procedures (Pisarev et al 2007). Then, individual purified components were incubated with 32 P-labeled vFLIP IRES before conducting filter-binding assays to analyze the affinity and specificity of putative interactions (Willcocks et al 2011). We determined that the vFLIP IRES binds the 40S subunit with an apparent equilibrium dissociation constant (K d ) of 28 nM, while the CSFV IRES (as a control) bound with an affinity of 8 nM (Fig.…”
Section: Vflip Ires Directly Interact With the Ribosomes And Eifsmentioning
confidence: 99%
“…The c-myc IRES was kindly provided by Anne E. Willis (MRC Toxicology Unit, University of Leicester) and the IRES sequence from encephalomyocarditis (EMCV, nucleotides 406-930) and hepatitis C virus (HCV; nucleotides 1-426) were described previously (Easton et al 2009). For in vitro translation, the IRES fragments were cloned into the pGEM-CAT/LUC plasmid described previously which encodes chloramphenicol acetyltransferase (CAT) and firefly luciferase (fLUC) under the control of a T7 promoter (Willcocks et al 2011). The sequence of the stem-loop sequence inserted upstream of the IRES is 5 ′ -CAGATCTACGCGGTTCGCCGCGTAGATCTG-3 ′ .…”
Section: Plasmidsmentioning
confidence: 99%
See 2 more Smart Citations